2018
DOI: 10.1177/1468017318815293
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a social work professional after incarceration

Abstract: Summary This article is based on data collected from interviews conducted with past and present members of a higher education program that affords previously incarcerated individuals the chance to attend a four-year university. College participation postincarceration can help foster trajectories for crime avoidance and employment. Less specific attention has been paid to how such educational experiences might shape opportunities for released prisoners to become professional help-givers and also help themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The presence of people with experience of incarceration acting in helping roles has the capacity to challenge these widespread negative stereotypes surrounding those who have engaged in criminal activity (Runell, 2018). Helpers with lived experience can alter the dominant discourse from one of 'spoiled identity' to one of 'survivor', 'champion' and 'advocate for change' (Lebel, 2007;Leverentz, 2014;Weaver and Weaver, 2013).…”
Section: Stigma and Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of people with experience of incarceration acting in helping roles has the capacity to challenge these widespread negative stereotypes surrounding those who have engaged in criminal activity (Runell, 2018). Helpers with lived experience can alter the dominant discourse from one of 'spoiled identity' to one of 'survivor', 'champion' and 'advocate for change' (Lebel, 2007;Leverentz, 2014;Weaver and Weaver, 2013).…”
Section: Stigma and Discriminationmentioning
confidence: 99%
“…This process can also occur at a personal level for helping professionals as '... the social processes involved with becoming a social service provider post incarceration are also atypical in that the helper's own criminal history is destigmatized and reconstructed as a benefit rather than hindrance to the functioning of society' (Runell, 2018, p. 2). Runell (2018) suggested that this involved a process of 'reversing socially imposed criminal stigmas' (p. 4). Being 'out in the open' about lived experiences of incarceration challenged the stigmatising discourse, influencing public perceptions as well as helping other formerly incarcerated persons heal trauma associated with stigmatisation (Heidemann et al, 2014;Leverentz, 2014;Weaver and Weaver, 2013) The literature identified both the positive and negative impacts that professional 'helpers' with lived experience of incarceration can have upon stigma (including internalised stigma) on both the 'helper' and those being 'helped'.…”
Section: Stigma and Discriminationmentioning
confidence: 99%
“…As a special group, the employment of prisoners has received widespread attention from society. It is common for released prisoners to apply for jobs (Runell, 2020), but in fierce employment competition, prisoners being isolated from society for a long time and various factors such as social prejudice and other aspects have huge impacts on their job hunting. According to the survey, in Japan, 40% of the elderly released from prison reoffend within 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Professional development of social workers is critical to competent practice with clients. While the literature contains articles about the motivations of those entering the profession (Runell, 2020), scholarly works that examine the career progression of practicing social workers are more difficult to find. The lack of guidance provided to social workers as they transition from students to practitioners is surprising as the responsibilities required to provide competent care are numerous and the workplace stressors are significant (Burghardt, 2021;NASW, 2021a).…”
mentioning
confidence: 99%